Dynamiques du développement de la pisciculture dans deux régions du Brésil : une approche comparée - Rodrigues da Silva, Newton Jose; Beuret, Jean-Eudes; Mikolasek, Olivier; Fontenelle, Guy; Dabbadie, Lionel; Lazard, Jerome; Espagnoli Geraldo Martins, Maria Inez [UNESP] (John Libbey Eurotext Ltd, 2009)
Based on a historical approach, fish farming development was compared in two differentiated Brazilian areas. This study mobilizes the concept of Innovative Local System (ILS) together with the theoretical framework of the Sociology of Innovation and of the Economies of Size. We found that all the relationships within Ribeira Valley are mainly commercial based. There is neither coordination nor linking actions among the components of ILS. Hence, the "network" was unable to create technological or organizational innovations capable of facing any economic crisis. Conversely, in the Itajai High Valley, the socio-technological fish farming network has been developed on social, commercial, and trustful relationships. All interactions among the components of the ILS were coordinated to each other which allowed this network to react when economic or climatic threats threatened the sustainability of fish farming.
The dynamics of fish farming development in two Brazilian valleys: A comparative approach
Keywords: Brazil; fish culture; innovative local systems; sociology of innovation